PENGARUH NILAI KURS DOLLAR AS DAN SUKU BUNGA SBI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) TAHUN 2010-2012 - Anugrahati, Citra; Endah Dwianti (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2020)
This study aims to determine the effect of US dollar exchange rates and SBI interest rates on the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange (BEI) from 2010 to 2012. The variables used in this study are the US Dollar exchange rate and the SBI interest rate. This research is a type of causal research and a replication of previous studies with the research population in the form of the Composite Stock Price Index (IHSG) which is listed on the Indonesia Stock Exchange in 2010-2012. The data used are secondary data, the value of the US dollar exchange rate and the SBI interest rate as independent variables and the Composite Stock Price Index (IHSG) as the dependent variable. The statistical method used is multiple linear regression with 36 samples of data, by first doing the classical assumption. The results of this study prove that simultaneously the US Dollar Exchange Rate The SBI Interest Rate has a positive and significant effect on the Composite Stock Price Index (IHSG). This can be proven by the results of the analysis Fcount> Ftable which is equal to (9,562> 3,29). The R2 value is only 36.7% and the remaining 63.3% is influenced by other factors outside the independent variable. Partially, this study shows that the US Dollar Exchange Rate and the SBI Interest Rate have a negative and significant effect on the Composite Stock Price Index (IHSG).